Hitchcock and homosexuality : his 50-year obsession with Jack the Ripper and the superbitch prostitute : an psychoanalytic view. - Price, Theodore (London [?] : The Scarecrow Press, 1992)
Fonds Suzan Daniel (FSD)
Engels
Monografie